Shattered - Kureishi, Hanif 1954- (Hamish Hamilton, an imprint of Penguin Books, 2024)
"On Boxing Day 2022, in Rome, Hanif Kureishi had a fall. When he came to, in a pool of blood, he was horrified to realise he had lost the use of his limbs. He could no longer walk, write or wash himself. He could do nothing without the help of others, and required constant care in a hospital. So began an odyssey of a year through the medical systems of Rome and Italy, with the hope of somehow being able to return home, to his house in London. While confined to a series of hospital wards, he felt compelled to write, but being unable to type or to hold a pen, he began to dictate to family members the words which formed in his head. The result was an extraordinary series of dispatches from his hospital bed - a diary of a life in pieces, recorded with rare honesty, clarity and courage. This book takes these hospital dispatches - edited, expanded and meticulously interwoven with new writing - and charts both a shattering and a reassembling: a new life born of pain and loss, but animated by new feelings - of gratitude, humility and love."--